The effect of inner diaphragms and continuous sill selection of automotive B-pillar - Tan, Chee Fai; Md Radzai , Said; Shamsul Anuar, Shamsudin (2006)
This paper discusses in detail on the behaviour of T-frame under specific loading obtained experimentally to investigate the deflection of the vehicle B-pillar. A series of T frame were designed with inner diaphragm at various location in the sill member in order to investigate the effect of inner diaphragm and non-continuous closed hat section in the sill member. These two types of specimens were employed to show the effects of different types of sill member on the stiffness of the overall structure. The finite element analysis and experimental test were carried out on the in-plane bending. The experimental results were compared with the finite element analysis results to demonstrate the effectiveness of the inner diaphragm in the automotive 8-pillar. Based on the results obtained from the experimental work, location of baffles for the specimens do not gives any major influences for in-plane bending case due to the shape and direction baffles are not .suitable. From the results, the specimen with baffles located at the weld line is stiffer than the other specimens.